Liability insurance as a (social) response to the changing regulatory framework: From prohibited to compulsory - Petrović-Tomić Nataša (Anali Pravnog Fakulteta u Beogradu)
The article analyzes the relationship between the institutions of liability and liability insurance, aimed at identifying the modalities of their interaction. Insurance indisputably affects the development and scope of tort law, but this influence is not one-sided. At the present development level it has been noted that liability insurance also plays an indispensable role in indemnity litigation. The development path of liability insurance shows that the developed legal order entails two mutually compatible systems. Whilst objective liability for damages is the response to numerous activities that render realistic the possibility of causing damage to others, regardless of whether the damage could have been avoided through cautious behavior, liability insurance is the response to the changed regulatory framework, which leads to liability reaching unprecedented proportions. Therefore, the author concludes that insurance does not threaten to substitute the principle of compensatory damages with the logic of loss-spreading.